Direct data transfer over the host controller interface of the Bluez Bluetooth protocol stack in Bayanihan Linux V2.0 - Cheung, William R.; Fallorina, Joel T.; Ballesteros, Janice M.
The Bluetooth specification defines a whole protocol stack necessary for a standardized interface of different Bluetooth devices. One of the layers in the stack is the Host Controller Interface (HCI). It serves a vital role in interfacing the higher and the lower parts of the stack. This paper discusses the implementation, setup and testing processes involved in directly utilizing the HCI layer in sending and receiving data. An application was developed on top of Bayanihan Linux v2.0 which has built-in Bluez, the official Linux Bluetooth protocol stack. The application shows the operations and functions of the HCI layers in transferring data. Accessing the HCI layer directly will have several advantages, one of which is the reduced overhead from higher layers. The setup was tested with a 3COM USB Adapter and a 3COM PCMCIA Card.
Keywords: Bluetooth; Bayanihan Linux; BlueZ; Host Controller Interface